Pedagogical dimensions for the promotion of citizenship within social control - Giovanni Gurgel Aciole; Evanir Brunelli (Interface: Comunicação, Saúde, Educação, 2007)
This paper is about the social control practices found in the Brazilian National Health Care System (SUS) regarding its pedagogical dimensions. Social control practices have been deemed as alternatives to direct democracy and as a space for the defense of public interests in health care policies. The thought over the action of health councils recognizes the difficulties generated by conflicts and tensions brought forth by both individual and collective interests, ranging from individuality culture to citizenship relations. In addition, it encompasses the issue of power in its manifold manifestations. However, building social control in SUS means to maintain empowerment and overcome tensions and conflicts between both individual and citizen. At last, such aspects are thought to be pedagogical components to be explored for the construction of citizenship and democracy, and to improve social as well as public control in SUS.